MODELING OF THE ZONES OF INFLUENCE OF GAS WELLS AT A DEPLETED RESERVOIR - Ioan Alexandru Stoica; Lazăr Avram; Bogdan Simescu; Mihaela Helstern (Romanian Journal of Petroleum & Gas Technology, 2024)
Modeling the behavior of natural gas wells during exploitation is often an essential step in studying the evolution of natural gas production. However, the theoretical simulation models of wells placed on depleted deposits usually gave results different from the reality in the field. This was due to problems with the integrity of the productive strata, especially with the degree of sealing of the existing wells. The present work attempts to develop and carry out a rigorous research program of a deposit from the Sarmatian deposits of the Transylvania basin. In the paper it is presented a theoretical framework through which the behavior of the depleted field can be followed by discretizing the field and setting some discrete properties (in the case present the deposit pressure), which by expanding the modeling can serve to identify poorly drained areas, which can be exploited in the future, contributing to the increase of the final recovery factor. This discretization was achieved through the system of grid blocks, for which the average properties (temperature, pressure, permeability, etc.) and connectivity between them were modeled through the flow coefficients. The theoretical model applied to the particular deposit, which can be extended for future production provisions, by setting time intervals e.g. to a month/year instead of days and extending the grid over the entire surface of the field, not only for the central area, where the wells are grouped.